Tradisi dalam Arak-Arakan: Kajian Komparatif Grebeg Suro di Indonesia dan Gion Matsuri di Jepang : Traditions in Processions: A Comparative Study of Grebeg Suro in Indonesia and Gion Matsuri in Japan - Indah Puspita Sari (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
Communities in various regions have traditions that are carried out annually. The procession tradition is one of the cultural practices performed by both the Javanese community and the people of Kyoto, Japan. The Javanese community conducts a procession tradition during the Grebek Suro celebration, while the people of Kyoto parade decorated floats during the Gion Matsuri festival. The purpose of this study is to compare the similarities and differences between the procession traditions of Grebek Suro and Gion Matsuri. The research employs a qualitative method with data collection conducted through library research. The theoretical framework used is Koentjaraningrat’s theory of religion, which consists of five elements.The results show that the procession traditions of both Grebek Suro and Gion Matsuri represent the communities’ efforts to preserve ancestral cultural heritage. These traditions function as expressions of gratitude for harvest yields and as prayers to prevent outbreaks of disease.In conclusion, both traditions serve not only as forms of cultural expression and religious ritual, but also as means of strengthening social solidarity and maintaining the continuity of traditional values amid changing times.